Minisuperspace quantum cosmology in f(Q) gravity - Francesco Bajardi; Salvatore Capozziello (European Physical Journal C: Particles and Fields, 2023)
Abstract f(Q) symmetric-teleparallel gravity is considered in view of quantum cosmology. Specifically, we derive cosmological equations for f(Q) models and then investigate the related energy conditions. In the Minisuperspace formalism, the point-like f(Q) Hamiltonian is taken into account. In this framework, we obtain and solve the Wheeler–De Witt equation, thus finding the wave function of the universe in different cases. We show that the Hartle criterion can be applied and classical observable universes occur.